(untitled) (Acta Scientiarum. Biological Sciences, 2013)
Oxidative stress is an imbalance between reactive oxygen species and antioxidant capacity of action. Thus, research, alternative to mitigate the damaging effects of oxidative stress, improving the body´s antioxidant capacity, prevented the disease and its complicatons. The leaves and fruits of guava are rich in the antioxidants. This work aimed to study the effect of flour and ethanolic/acetone extracts leaves and fruits of guava on lipid oxidation in rats with hypercholesterolemic. The flour and extracts decreased leves of triglycerides and non – HDL cholesterol and increased in the HDL. Cholesterol levels decreased only leaves and fruits. The activity of GPx decreased in samples serum in all treatments and the SOD only the extracts were effective. There was no difference in levels the MDA in relation hypercholesterolemic control. For the samples of liver, there was no difference in activity SOD. In relation of activity GPx, only the flour was effective. There were differences in levels the MDA of the hypercholesterolemic animals treated with flour and extracts with the animals of the hypercholesterolemic control.